Reformulation of income transfers in Brazil: Simulations and challenges - Luís Henrique Paiva; Letícia Bartholo; Pedro H. G. Ferreira de Souza; Rodrigo Octávio Orair (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
This One Pager presents simulations for the future of non-contributory transfers in Brazil, discussing the dilemmas of various designs and estimating costs and possible impacts on poverty and inequality. The authors also analyse a series of operational and budget-related challenges to implementation.
Keywords: 330; Inequality; poverty; income transfers